Elements of sourcing strategies in FM services – a multiple case study - Ventovuori, Tomi (International Journal of Strategic Property Management, 2010)
The aim of this paper is to identify the different elements of the sourcing strategy decision‐making process and to clarify what are the factors that lead to the selection of a certain sourcing strategy in FM services. The study is based on a literature review and a multiple case study, which was conducted with four organizations representing different types of FM service clients. To find the optimal sourcing strategy and understand the consequences of different sourcing options, five decision categories must be analysed: sourcing interface, organizational decision‐making, the scope of service package, the geographical area of sourcing and relationship type. There are also some other elements that must be taken into account in the process of sourcing strategy development such as different elements of business in general and the prevailing market conditions. It is strongly suggested that companies could apply the presented integrated approach as a starting point for the development of sourcing strategies in FM services. In addition, this study shows that companies should view the development of sourcing strategies as an important phase of the procurement cycle. First Published Online: 18 Oct 2010